Enhancing self-acceptance in middle-aged patients with hypertension through dhikr relaxation therapy - Puteri, Gita Anindya; Nashori, Fuad; Ramdani, Zulmi (Jurnal Ilmiah Psikologi Terapan, 2025)
Hypertension, characterized by a persistent elevation of systolic and diastolic blood pressure above 140/90 mmHg, is often referred to as a silent killer due to its asymptomatic nature and tendency to be detected only after complications arise. This study examines the effectiveness of dhikr relaxation therapy in enhancing self-acceptance among middle aged adults with hypertension. A quasi experimental design was employed, involving 20 hypertensive patients (5 males and 15 females) recruited through purposive sampling from the Kratonan Community Health Center in Surakarta, Indonesia. Participants were randomly assigned to either an experimental group (receiving dhikr relaxation therapy) or a control group (receiving no intervention), with 10 individuals in each group. The Self-Acceptance Scale was used to assess participants’ levels of self-acceptance. Hypothesis testing using the Friedman test indicated a statistically significant improvement in self-acceptance following the intervention (p = 0.002). These findings suggest that dhikr relaxation therapy is effective in promoting self-acceptance and reducing stress among individuals with hypertension. The study recommends that healthcare practitioners might consider incorporating dhikr relaxation techniques into routine care through structured training programs, as a means to enhance psychological well-being and support better health outcomes in hypertensive populations.